The effect of ulexite to the tribological properties of brake lining materials. Issue 1 (16th March 2016) - Sugozu, Ilker; Mutlu, Ibrahim; Sugozu, Kezban Banu
Abstract : Recently, different brake pads have started to be investigated in brake friction industry by replacing the asbestos with new materials. This paper presents the role of Ulexite on friction assessment and screening Test of newly formulated brake pads. Friction coefficient, specific wear ratio, and scanning electron microscope SEM for friction surfaces were examined to assess the performance of brake pads. From the results, they concluded that the friction material containing Ulexite improved friction stability and fade resistance. Further, for heat treated samples they claimed a higher and stable friction coefficient. POLYM. COMPOS., 39:55–62, 2018. © 2016 Society of Plastics Engineers